Particle Swarm Optimization for Resource Constrained-project Scheduling Problem with Varying Resource Levels. (2016) - Joy, Jiby; Rajeev, Srijith; Narayanan, Vishnu
Abstract: This paper proposes Particle swarm optimization for resource constrained project scheduling problem with varying resource levels (RCPSPVRL). RCPSPVRL uses resources of limited availability but varying predetermined levels. The activities are of known durations and resource requests, linked by precedence relations. In project scheduling problems, project activities are assumed to have constant resources throughout the entire project duration. In RCPSPVRL, resources are not kept constant, the total project duration is divided in to different time periods, within a particular time period the quantity of resources are kept constant and the quantity of resources can be varied on various time periods. The objective is to schedule the activities in such a way that effective utilization of resources are made by utilizing varying resource levels. RCPSPVRL is tested by using CPLEX ILOG optimization studio and is validated by using PSO on MATLAB 2014.